2017
DOI: 10.1007/s00234-017-1791-5
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing subtle near-occlusion in carotid stenosis patients: a computed tomography angiographic study

Abstract: The utilization of 1.0 mm cut-off value for the intra-individual distal ICA LD side-to-side difference to distinguish atherosclerotic ICA near-occlusion leads to a relatively high incidence of near-occlusion. In CTA, recently suggested to be used for near-occlusion diagnosis, a discriminatory 1.0 mm cut-off value could function as a pragmatic tool to enhance the detection of even subtle near-occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In prognostic and management studies, separation of nearocclusion and conventional ≥ 50% carotid stenoses is made by assessing several features of near-occlusion [3][4][5]. Koskinen et al recently suggested that a ≥ 1.0-mm side-to-side difference in ICA diameter could be used to separate near-occlusion and conventional ≥ 50% stenosis [6]. However, asymmetry in the ICA caused by Circle of Willis (CoW) variation can also be associated with a 1.0-mm side-to-side difference of extracranial ICA diameter and mimic near-occlusion when coinciding with stenosis ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In prognostic and management studies, separation of nearocclusion and conventional ≥ 50% carotid stenoses is made by assessing several features of near-occlusion [3][4][5]. Koskinen et al recently suggested that a ≥ 1.0-mm side-to-side difference in ICA diameter could be used to separate near-occlusion and conventional ≥ 50% stenosis [6]. However, asymmetry in the ICA caused by Circle of Willis (CoW) variation can also be associated with a 1.0-mm side-to-side difference of extracranial ICA diameter and mimic near-occlusion when coinciding with stenosis ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the measurement and decision making mostly rely on CTA and/or magnetic resonance angiography imaging. 32,33 Other imaging features, such as plaque area on computerised plaque analyses, 34 intraplaque haemorrhage Figure 5. The development of stroke prevention potential at Helsinki University Hospital (HUH).…”
Section: Grade Of Stenosis and Plaque Characteristicsmentioning
confidence: 99%
“…It is also important to interpret what is seen, such as whether side-to-side asymmetry is likely due to uniform collapse or something else such as old dissections or anatomical variance. An example of the interpretive approach using the illustrated case in the new article [1] is that there is a clearly visible side-to-side difference with uniform collapse where the distal artery otherwise seems normal (A + C), small absolute ICA size (B and provided measurement), ICA similar to ECA (A + C), and stenosis hard to assess due to calcifications. The interpretation of these findings is a nearocclusion without full collapse, and the interpretation seems certain from available information (even though the stenosis could not be clearly assessed, but it could be impressive).…”
Section: Interpretative Approach To Near-occlusion Diagnosismentioning
confidence: 99%
“…
In this issue of Neuroradiology, Koskinen and colleagues present their idea: that carotid near-occlusion (a tight stenosis that causes a collapse of the distal artery) can be separated from conventional ≥50% stenosis by measuring the distal diameter and all cases with ≥1.0 mm side-to-side difference is a nearocclusion [1]. Their goal was Bto facilitate the recognition and diagnosis of near-occlusion, and raise the notion that even when a subtle distal ICA LD [Luminal Diameter] reduction is present, a possible near-occlusion should be considered.^It is important to raise awareness of near-occlusions without full collapse, when the distal artery otherwise seems normal, albeit smaller than usual.
…”
mentioning
confidence: 99%